(untitled) (Physical Education, Health and Social Sciences, 2026)
Epilepsy is a neurological disorder characterized by recurrent seizures. Seizures occur due to sudden abnormal electrical activity in the brain. Usually, the exact causes of epilepsy are may not be known but there are several known factors and potential causes (genetic factors, brain injuries, brain tumors, stroke, brain infection, developmental disorders, metabolic disorders, perinatal injuries, vascular abnormalities, Alzheimer’s disease and Dementia) can contribute in the development of epilepsy. The worldwide prevalence of epilepsy is estimated is 7.60 per 1000 people, it may varies between countries and regions. Low and middle-income countries tend to have high prevalence comparatively to high-income countries, due to limited access to healthcare and higher rates of risk factors such as head injuries and infections. The reported prevalence of epilepsy in Pakistan is 9.96 per 1000 people. The treatment of epilepsy is generally a combination of medications, adjustments in lifestyle, and in certain instances, surgical procedures. The treatment objective is to decrease the occurrence and intensity of seizures while mitigating adverse effects and enhancing overall quality of life. We collected 11 effected samples from the Hazara division. The clinical characteristics and medical history of each patient were recorded and the samples were sent to UCL UK for genetic analysis, to understand the cause of the disorder. We used whole exome sequencing for the identification of mutation in DNA and later on used CRISPR technology to see whether the changes are reversible or not. For this purpose, animal models are being used like Mouse and Drosophila models in Germany and Italy in collaborating groups. We are waiting for the genetic analysis. A survey among 110 students was also conducted to know public perspective about Epilepsy in studied group.